COMPARAÇÃO ENTRE SOFTWARES DE CÁLCULO NUTRICIONAL DE DIETAS - Daniela de Brito Trindade; Raquel Machado Schincaglia; Lorraynne Barbosa de Assunção; Sarah Jhayse de Araújo Lima; Maria do Rosário Gondim Peixoto (Universidade do Estado do Rio de Janeiro, 2018)
The choice of the ideal software is essential to assist the development of the specific conduct. So this study evaluates the agreement of three softwares for nutritional calculation of diets, by comparing the nutritional composition of 100 24-hour recalls and the functional characteristics evaluated in the three programs. Observational study, which analyzed the characteristics and tools available in three calculation programs: DietWin Professional Plus® - version 2.0 Avanutri Online® and WorldFood Dietary Assessment System®. From the diets calculated in the three programs, it was possible to compare the characteristics of functionality, reliability, usability, efficiency and portability. There was similarity in the functional characteristics of the national programs, as opposed to the American one, which presented different differences and absence of a great number of characteristics analyzed. The study shows that the programs presented differences in their tools and characteristics. However the intention of the research work was not to make inference about their qualities, but only to help the professional in choosing the one that best identifies with his professional practice. DOI: 10.12957/demetra.2018.29706